2019
DOI: 10.1093/mmy/myy150
|View full text |Cite
|
Sign up to set email alerts
|

Comparative antifungal susceptibility analyses of Cryptococcus neoformans VNI and Cryptococcus gattii VGII from the Brazilian Amazon Region by the Etest, Vitek 2, and the Clinical and Laboratory Standards Institute broth microdilution methods

Abstract: Early diagnosis, efficient clinical support, and proper antifungal therapy are essential to reduce death and sequels caused by cryptococcosis. The emergence of resistance to the antifungal drugs commonly used for cryptococcosis treatment is an important issue of concern. Thus, the in vitro antifungal susceptibility of clinical strains from northern Brazil, including C. neoformans VNI (n = 62) and C. gattii VGII (n = 37), to amphotericin B (AMB), 5-flucytosine, fluconazole, voriconazole, and itraconazole was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
1
10
0
2
Order By: Relevance
“…The environmental triazole (tebuconazole) used as an agrochemical pesticide may induce cross-resistance to clinically available azoles in C. neoformans and C. gattii [ 16 ]. Moreover, it is noteworthy that a high frequency of C. neoformans isolates with non-wild-type (non-WT) susceptibility to AMB has been reported [ 17 , 18 ]. However, routine antifungal susceptibility testing (AST) is not performed in most microbiological laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental triazole (tebuconazole) used as an agrochemical pesticide may induce cross-resistance to clinically available azoles in C. neoformans and C. gattii [ 16 ]. Moreover, it is noteworthy that a high frequency of C. neoformans isolates with non-wild-type (non-WT) susceptibility to AMB has been reported [ 17 , 18 ]. However, routine antifungal susceptibility testing (AST) is not performed in most microbiological laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…The major agents of cryptococcosis are members of C. neoformans and C. gattii complex. This complex was recognized in 2015 into seven species, based on phenotypic and genotypic, geographic, epidemiological and virulence characteristics [8][9][10][11][12][13][14][15]. The new classification includes the species C. neoformans sensu strictu (s.s) (genotype VNI/VNII/VNB), hybrids between C. neoformans and C. deneoformans (genotype VNIII) and C. deneoformans (genotype VNIV), and C. gattii complex is formed by C. gattii s.s (VGI), C. deuterogattii (VGII), C. bacillisporus (VGIII), C. tetragattii (VGIV), and C. decagattii (VGIIIc/ VGIV) [8,16].…”
Section: Introductionmentioning
confidence: 99%
“…Gradient diffusion methods are usually used as its substitute due to the easiness in performance and in the determination of MIC values. The usefulness of gradient diffusion methods is already described for Candida and Cryptococcus species [18,19], but for other fungi, the gradient diffusion MICs do not correlate with the gold standard method [20]. This study has shown that Etest® can be a fast and reliable methodology for the MIC v al u e s' d e t e r m i n a t i o n of a m p h o t e r i c i n B a n d voriconazole against R. mucilaginosa and thus, it could be applied to a diagnosis laboratory routine as well as to the epidemiological resistance surveillance.…”
mentioning
confidence: 99%